Predictors of depression, anxiety and stress during the first wave of the COVID-19 pandemic: The results of an online survey in Serbia - Opanković, Ana; Latas, Milan; Ristic, Ivan; Jerotic, Stefan; Bukumiric, Zoran; Lalovic, Nikola; Milovanovic, Srdjan (Engrami, 2022)
Background: The outbreak of the COVID-19 pandemic has affected the mental health of the population worldwide.Aim: Assessment of risk factors for symptoms of anxiety, depression, and stress during the first wave of the COVID-19 pandemic.Methods: An online survey including 161 participants was conducted in a population of both healthy participants and people who tested positive to COVID-19. The survey collected socio-demographic data, knowledge about the pandemic, psychological impact, and mental health status of the participants. The psychological impact on mental health status was assessed using the Depression, Anxiety, and Stress Scale (DASS-21). Logistic regression was used to determine the risk factors that increased the likelihood of having symptoms of depression, anxiety, and stress.Results: A total of 63.8 % of participants showed symptoms of anxiety, with 31.6% showing moderate symptoms of anxiety. Symptoms of depression were found in 44.1% of the sample, with 23.7% showing moderate symptoms of depression, according to DASS-21 cut-off criteria. No mental health history, a positive test for COVID-19, physical health status, and time point of assessment were the most significant factors predicting symptoms of depression. In relation to symptoms of anxiety, we observed the importance of physical health, having offspring and testing positive for COVID-19, and being male. Factors that influenced higher degrees of stress were: testing positive for COVID-19, special nutrition, having offspring, and being of low physical health.Conclusion: Our study indicates that during the COVID-19 pandemic in Serbia several factors could be important for the development of stress, depression, and anxiety and can be used as a basis for larger, population-based studies. Based on such future studies, evidence-based preventive mental health measures could be implemented in Serbia.
Keywords: mental health; COVID-19; DASS